2011
DOI: 10.1063/1.3668603
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio based polarizable force field generation and application to liquid silica and magnesia

Abstract: We extend the program potfit, which generates effective atomic interaction potentials from ab initio data, to electrostatic interactions and induced dipoles. The potential parametrization algorithm uses the Wolf direct, pairwise summation method with spherical truncation. The polarizability of oxygen atoms is modeled with the Tangney-Scandolo interatomic force field approach. Due to the Wolf summation, the computational effort in simulation scales linearly in the number of particles, despite the presence of el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…This means that for small magnitudes of the wave vectors k, the charge structure factor is also small. In previous studies 16,23 it was shown that the reciprocal-space term is indeed negligible compared to the real-space part, provided that the splitting parameter κ is chosen small enough. As however a smaller κ results in a larger real-space cutoff r c , the latter has to be chosen three or four times the size of a typical shortrange cutoff radius in metals.…”
Section: B Wolf Summationmentioning
confidence: 99%
See 4 more Smart Citations
“…This means that for small magnitudes of the wave vectors k, the charge structure factor is also small. In previous studies 16,23 it was shown that the reciprocal-space term is indeed negligible compared to the real-space part, provided that the splitting parameter κ is chosen small enough. As however a smaller κ results in a larger real-space cutoff r c , the latter has to be chosen three or four times the size of a typical shortrange cutoff radius in metals.…”
Section: B Wolf Summationmentioning
confidence: 99%
“…As however a smaller κ results in a larger real-space cutoff r c , the latter has to be chosen three or four times the size of a typical shortrange cutoff radius in metals. In a recent study 16 a cutoff radius of only 8Å was sufficient to describe the electrostatics of liquid silica and magnesia accurately. In addition, a continuous and smooth cutoff of the remaining screened Coulomb potentialẼ qq (r ij ) = q i q j erfc(κr ij )r −1 ij is adopted at r c by shifting the potential so that it goes to zero smoothly in the first two derivatives at r = r c .…”
Section: B Wolf Summationmentioning
confidence: 99%
See 3 more Smart Citations